Some Studies on the Seasonal Abundance of Tabanids in Nyala- Southern Darfur State - Sudan - Malik, Adam, M. E.; H., Khitma; A.H., Abdelrhman (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted to determine the seasonal abundance of tabanid flies in South Darfur using traps and fly patrol team using hand nets. Modified Epsilon traps were deployed in Nyala along Wadi Nyala (seasonal valley stream) during the period, September 2002 to August 2004. The species composition of tabanid flies caught were Tabanus sufis (55.9%), Atylotus spp.(41.4%), T.taeniola (4%), T.biguttatus (3.2%) and Philoliche magrettii (0.27%). The highest abundance of tabanids was during September, October and November of the year. The hand nets were found more efficient than traps in catching T.biguttatus and T.taeniola from resting sites. The findings of population peak of the most species particularly T. suifis and Atylotus spp. in rainy and early cold dry seasons suggest the risk and importance of mechanical transmission in the epidemiology of animal trypanosomosis in the region during these seasons. Control strategies may rely in deploying insecticides impregnated traps ,pour on and desiccation tabanid larvae habitat. Further studies on the evaluation of different tabanids traps such as conventional one catching only host seeking female with liquid captures water seeking male and female is highly recommended to avoid bias of conventional tabanid traps.